Corrigendum to “Kidney involvement in Rosai-Dorfman disease.” Kidney International 2023;103:231–232 (Kidney International (2023) 103(1) (231–232), (S0085253822008006), (10.1016/j.kint.2022.09.005)) - Mazzariol, Martina; Peyronel, Francesco; Fagni, Filippo; Minervini, Andrea; Santi, Raffaella; Agostini, Simone; Vaglio, Augusto (Kidney International, 2024)
DOI of original article: 10.1016/j.kint.2022.09.005 The authors regret that affiliation 2 was incorrectly displayed. This has been corrected in the article online. The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2024-06-21